Penerapan Self Organizing Maps dalam Pengelompokkan Provinsi di Indonesia Berdasarkan Aspek Pendidikan - Muhammad Fariz Faqih; Ilham Faishal Mahdy (Jurnal Riset Statistika, 2024)
Abstract. Indonesia participated in the Programme for International Student Assessment (PISA) in 2018, a global study that evaluates education systems in 70 countries. However, the 2020 Socio-Economic Survey, as reported in the 2020 Education Statistics, indicated that Indonesia has not yet achieved full success in its compulsory education program at the high school level, with a Gross Enrollment Ratio still below 95% and 1.13% of the population failing to complete education at that level. This study focuses on clustering education in Indonesia based on provinces and educational aspects. The study aims to cluster provinces in Indonesia using the Self Organizing Maps (SOM) method, a technique within Artificial Neural Networks used for clustering. The data used in this study comes from 34 provinces in 2023. The performance of the clustering model is evaluated using the Davies-Bouldin Index. The study identifies that the optimal number of clusters is two, with the first cluster consisting of 32 provinces and the second cluster consisting of 2 provinces. This research provides a deep understanding of the distribution and characteristics of education across various provinces in Indonesia, which can assist in future educational planning and policy-making. Abstrak. Indonesia berpartisipasi dalam Programme for International Student Assessment (PISA) pada tahun 2018, sebuah studi global yang mengevaluasi sistem pendidikan di 70 negara. Namun, Survei Sosial Ekonomi 2020, sebagaimana dilaporkan dalam Statistik Pendidikan 2020, menunjukkan bahwa Indonesia belum mencapai keberhasilan penuh dalam program wajib belajar di tingkat SMA, dengan Angka Partisipasi Kasar yang masih di bawah 95% dan 1,13% dari populasi gagal menyelesaikan pendidikan di tingkat tersebut. Artikel ini berfokus pada pengelompokkan pendidikan di Indonesia berdasarkan provinsi-provinsi di Indonesia dan aspek-aspek pendidikan. Artikel ini bertujuan untuk mengelompokkan provinsi-provinsi di Indonesia berdasarkan aspek pendidikan menggunakan metode Self Organizing Maps (SOM), sebuah metode dalam Artificial Neural Network yang digunakan untuk clustering. Data yang digunakan dalam artikel ini berasal dari 34 provinsi pada tahun 2023. Evaluasi performa model clustering dilakukan menggunakan Davies-Bouldin Index. Artikel ini mengidentifikasi bahwa jumlah klaster optimum adalah dua, dengan klaster pertama terdiri dari 32 provinsi dan klaster kedua terdiri dari 2 provinsi. Artikel ini memberikan pemahaman mendalam mengenai distribusi dan karakteristik pendidikan di berbagai provinsi di Indonesia, yang dapat membantu dalam perencanaan dan pengambilan kebijakan pendidikan di masa mendatang.